IMPROVING D-XYLOSE AND D-GLUCOSE CO-CONSUMPTION FOR BIOETHANOL PRODUCTION IN Saccharomyces cerevisiae DS71054 - DONNY RUDINATHA (NIM:20517017), YOSHUA
Bioethanol is an important renewable energy source that can be used to replace fossil fuels. Bioethanol has several advantages included reduced pollution, renewable energy, and easy starting material for production. First generation bioethanol production using agricultural stocks has drawn a negative connotation in Ã‚Â“Food vs FuelÃ‚Â” issues. Second generation bioethanol production was used to avoid this controversy using lignocellulose raw materials. These are mainly composed of 40% hexose sugar (D-glucose) and 20% pentose sugar (D-xylose). The yeast Saccharomyces cerevisiae is used for bioethanol production but cannot naturally utilize D-xylose as carbon source. This problem was solved by introducing xylose isomerase from fungi and overexpression of genes involved in pentose phosphate pathway. This allowed for D-xylose consumption, but only when all the D-glucose has been consumed. To improve the simultaneous consumption of D-glucose and D-xylose, evolutionary engineering of S. cerevisiae was conducted and a new strain, Evo6, was generated. Evo6 shows improved D-xylose consumption compared to the parental strain, albeit with decreased D-glucose consumption and therefore reduced growth rate. The main purpose of this research is to increase D-glucose consumption in Evo6 for better bioethanol production. Evo6 is a flocculating strain caused by significant upregulation of Flo1, a gene involved in flocculation. Upon the deletion of FLO1 gene, the flocculation was abolished. Evo6ΔFlo1, used in this research, shows improved sugar consumption rates compared to Evo6. Furthermore, RNAseq data indicates that in Evo6, Tsl1 and Tps3 are upregulated. These are genes involved in trehalose formation. One of the intermediates in this pathway is trehalose-6-phosphate which is an inhibitor of hexokinase that phosphorylates glucose into glucose-6-phosphate. Accumulation of trehalose-6-phosphate explains the lower D-glucose consumption by the Evo6ΔFlo1 strain. Indeed, upon the deletion of TPS3 or TSL1, using CRISPR-Cas9 system, improved D-glucose consumption and ethanol production was observed. Furthermore in Evo6, Hxt1 is significantly down regulated compared to the parental strain. Hxt1 is a low affinity D-glucose transporter that is expressed at high concentrations of D-glucose. Overexpression of Hxt1 in Evo6 resulted in enhanced D-glucose metabolism but a lower Dxylose consumption. Hxt1 overexpression level was confirmed using qPCR compared to actin expression level. Overexpression of Hxt1 was done by changing the promoter using CRISPRCas9 system. To further elucidate the increased of D-xylose consumption in Evo6, the Hxt37 transporter carrying the N367I point mutation, as found in the Evo6 strain, was overexpressed in the parental strain. The mutation converts Hxt37 from a D-glucose into a specific D-xylose transporter. Overexpression of Hxt37 N367I resulted in a significant decreased in D-glucose metabolism however only a limited increased in D-xylose consumption was observed. Overexpression of Hxt37 was done using a plasmid based system. Overall, these data show that in strains that carry out D-glucose and D-xylose co-metabolism, D-xylose metabolism lead to increased trehalose-6-phosphate production that limits D-glucose consumption.